2003
DOI: 10.1038/sj.bjp.0705351
|View full text |Cite
|
Sign up to set email alerts
|

Comparative regional haemodynamic effects of the nitric oxide synthase inhibitors, S‐methyl‐L‐thiocitrulline and L‐NAME, in conscious rats

Abstract: 1 The regional haemodynamic effects of the putative nNOS inhibitor, S-methyl-l-thiocitrulline (SMTC), were compared with those of the nonselective NOS inhibitor, N G -nitro-l-arginine methyl ester (l-NAME), in conscious, male Sprague -Dawley rats. 2 SMTC (0.3 mg kg À1 bolus) produced a significant, short-lived, pressor effect associated with renal, mesenteric and hindquarters vasoconstriction; the same dose of l-NAME did not affect mean blood pressure (BP), although it caused bradycardia and mesenteric vasocon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
44
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 45 publications
13
44
2
1
Order By: Relevance
“…Experiments began the day after catheter implantation. From previous studies using the approaches described here, we have seen no evidence of hangover effects of the anesthetic regimen (Wakefield et al, 2003;Woolard et al, 2004). Furthermore, in the present study, hemodynamic responses to vasoconstrictor and vasodilator challenges were consistent across the four experimental days in vehicle-infused rats (see Results).…”
Section: Methodssupporting
confidence: 61%
“…Experiments began the day after catheter implantation. From previous studies using the approaches described here, we have seen no evidence of hangover effects of the anesthetic regimen (Wakefield et al, 2003;Woolard et al, 2004). Furthermore, in the present study, hemodynamic responses to vasoconstrictor and vasodilator challenges were consistent across the four experimental days in vehicle-infused rats (see Results).…”
Section: Methodssupporting
confidence: 61%
“…10 Likewise, a comparison of the effects of systemic infusion of SMTC versus the nonselective NOS inhibitor L-nitroarginine methyl ester in rats in vivo showed that SMTC increased blood pressure and reduced renal blood flow at doses that did not induce such effects with L-nitroarginine methyl ester. 17 Although the above results suggested that local SMTC infusion reduced basal blood flow through the inhibition of nNOS, this assumption is based on the selectivity of SMTC for nNOS over eNOS reported by Furfine et al 10 and its greater potency at reducing basal forearm flow than L-NMMA. The original studies by Furfine et al 10,18 were performed on in vitro preparations, including rodent isoenzymes, whereas the present study aimed to investigate the role of nNOS in the human microvasculature in vivo.…”
Section: Seddon Et Al Nnos Regulates Human Basal Blood Flowmentioning
confidence: 85%
“…The use of isoform-selective NOS inhibitors is therefore crucial in such investigations. As discussed in detail elsewhere (12,13) and demonstrated by previous pharmacological studies (18,64) and the current hypotensive responses to ACh (Fig. 1), SMTC represents a viable tool for this purpose based on its selectivity for nNOS over both eNOS and iNOS inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Two separate contraction bouts were performed under control (1.2 ml heparinized saline) and selective nNOS inhibition (2.1 mol/kg SMTC dissolved in 1.2 ml heparinized saline) conditions. This dose of SMTC was selected based on previous studies designed to inhibit selectively nNOS in both humans and rodents (18,30,53,64) and our analysis of the highest possible SMTC dose that could be administered without affecting the hypotensive response to ACh, indicative of nonspecific eNOS inhibition (12,13). Each solution was infused at a rate of 0.2 ml/min into the tail artery catheter for a total time of 6 min, after which a ϳ2-min period was allowed for resting muscle PO2mv to stabilize.…”
Section: Methodsmentioning
confidence: 99%